2008
DOI: 10.17221/416-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic and mineral fertilisers on biological properties of soil under seminatural grassland

Abstract: Over 2004Over -2006, effects of mineral fertilisers (60 N + 30 P + 60 K kg/ha or 120 N + 30 P + 60 K kg/ha) and farmyard manure (12 or 24 t/ha) application on biological and chemical properties of soil were studied in seminatural grassland. The research trial was established at Radvaň site, central Slovakia (altitude 480 m, loamy to sandy-loamy Cambisol). These parameters were investigated during the growing seasons: CO 2 production, intensity of total N mineralisation (TMN), the rate of nitrification (NIT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…Our results are also in agreement with Haynes and Naidu (1998). However, some researchers demonstrated that application of manure increased the soil pH (Ondrášek and Čunderlík 2008). Lafayette et al (2009) reported that gypsum did not cause any significant change on the soil pH in acidic soils.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are also in agreement with Haynes and Naidu (1998). However, some researchers demonstrated that application of manure increased the soil pH (Ondrášek and Čunderlík 2008). Lafayette et al (2009) reported that gypsum did not cause any significant change on the soil pH in acidic soils.…”
Section: Resultsmentioning
confidence: 99%
“…Organic fertilisation, using particularly manure and compost, improves soil fertility by increasing the content of soil organic matter and the activity of soil microflora, and helps enhance the biological processes of soil. Ondrášek and Čunderlík (2008) concluded that the effects of fertilisers, especially manure application, on microbial parameters of soil were positive. The manure application enriches the soil not only with many organic substances but also with numerous forms of microorganisms enhancing and intensifying the biological activity of soil.…”
Section: Resultsmentioning
confidence: 99%
“…doi: 10.17221/7/2014-SWR Farmyard manure (FYM) is the main fertilizer maintaining soil potential fertility because with its application the soil receives biogenic elements that are assimilated by growing crops and thus removed from the soil (Repsiene & Skuodiene 2010). The manure application increases also soil pH (Ondrášek & Čunderlík 2008). Increasing of pH depends on the dose and timing of FYM application.…”
mentioning
confidence: 99%